Antimicrobial Activity of Marine Bacterial Symbionts Retrieved from Shallow Water Hydrothermal Vents - Eythorsdottir, Arnheidur; Omarsdottir, Sesselja; Einarsson, Hjorleifur (Marine Biotechnology, 2016)
Marine sponges and other sessile macro-organisms were collected at a shallow water hydrothermal site in Eyjafjörður, Iceland. Bacteria were isolated from the organisms using selective media for actinomycetes, and the isolates were screened for antimicrobial activity. A total of 111 isolates revealed antimicrobial activity displaying different antimicrobial patterns which indicates production of various compounds. Known test strains were grown in the presence of ethyl acetate extracts from one selected isolate, and a clear growth inhibition of Staphylococcus aureus was observed down to 0.1 % extract concentration in the medium. Identification of isolates shows different species of Actinobacteria with Streptomyces sp. playing the largest role, but also members of Bacilli, Alphaproteobacteria and Gammaproteobacteria. Sponges have an excellent record regarding production of bioactive compounds, often involving microbial symbionts. At the hydrothermal vents, however, the majority of active isolates originated from other invertebrates such as sea anemones or algae. The results indicate that antimicrobial assays involving isolates in full growth can detect activity not visible by other methods. The macro-organisms inhabiting the Eyjafjörður hydrothermal vent area host diverse microbial species in the phylum Actinobacteria with antimicrobial activity, and the compounds responsible for the activity will be subject to further research.